Novel cell surface markers identify routes to iPS cells - O'Malley, James (The University of Edinburgh, 2014)
The generation of induced pluripotent stem cells (iPSCs) presents a challenge to normal developmental processes. The low efficiency and heterogeneity of most methods have hindered understanding of the precise molecular mechanisms promoting, and roadblocks preventing, efficient reprogramming. While several intermediate populations have been described, it has proved difficult to characterize the rare, asynchronous transition from these intermediate stages to iPSCs. The rapid expansion of a minor population of reprogrammed cells can also obscure investigation of relevant processes. Understanding of the biological mechanisms essential for successful iPSC generation requires both accurate capture of cells undergoing the reprogramming process and identification of the associated global gene expression changes. Here we demonstrate that reprogramming follows an orderly sequence of stage transitions marked by changes in cell surface markers CD44 and ICAM1, and a Nanog-GFP reporter. RNA-sequencing (RNA-seq) analysis of these populations demonstrates two waves of pluripotency gene up-regulation, and unexpectedly, transient up-regulation of multiple epidermis-related genes, demonstrating that reprogramming is not simply the reversal of normal developmental processes. This novel high-resolution analysis enables the construction of a detailed reprogramming route map, and this improved understanding of the reprogramming process will lead to novel reprogramming strategies.
Keywords: Induced pluripotent stem cells; Reprogrammed cells